Unveiling French-African Memory - Boniface Mongo-Mboussa (Studies in 20th & 21st Century Literature, 2002)
Whereas the question of memory has become central to French identity, notably in regards to the Vichy period, French-African memory has been systematically obscured…
Keywords: French identity; memory; Vichy period; French-African memory; obscure; French memory